Interculturalidad en la educación médica en la Universidad del Cauca. - LÓPEZ-GARZÓN, NELSON ADOLFO (Acta Medica Colombiana)
The intercultural perspective in medical education in Latin America and Colombia is an inclusive process which must conquer challenges and barriers. These must be overcome by designing intercultural understanding programs and public policies with new trends in the training of university medical students. Instilling intercultural abilities in ethnic students within the healthcare sciences programs at Universidad del Cauca allows the visualization of a group of professionals with the skills to serve in their regions with social and cultural relevance, linking biomedical knowledge in a positive synergy with traditional medicine, building an alternative human and evaluative intercultural identity that cultivates the relationship between physicians and native and migrant patients.